Representasi Nilai-Nilai Keluarga dalam Film pendek Es Krim Terakhir dari Ayah di MOP Channel: Analisis Semiotika Charles Sanders Peirce - Nurul Lailatuz Zakiyah; Eka Nova Ali Vardani; Dzarna Dzarna (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This research aims to describe the representation of family values in the short film The Last Ice Cream from Dad through Charles Sanders Peirce's semiotic approach. The qualitative descriptive method was employed, with data collection techniques including comprehensive observation of the film, recording scenes and dialogues containing family values, and identifying the semiotic signs such as icons, indices, and symbols used within the film. Data was systematically recorded on data sheets and analyzed through data reduction, data presentation, and interpretation of meaning based on visual and verbal context in the film. The results indicate that the film effectively represents family values such as honesty, responsibility, hard work, discipline, and affection through the use of semiotic signs that form a strong visual and emotional narrative. These values are depicted through interactions of characters, visual symbols, and meaningful dialogues, emphasizing the significant role of family and the father figure in shaping moral and social character. This study concludes that films, especially short films, can serve as effective educational tools in instilling and strengthening family values within society. The findings support the development of character education media oriented towards family and cultural values to enhance the quality of character education in the nation.